2019
DOI: 10.33225/jbse/19.18.209
|View full text |Cite
|
Sign up to set email alerts
|

Item Dimensionality Exploration by Means of Construct Map and Categorical Principal Components Analysis

Abstract: The aim of this research is to study the merits and complementarity of Construct Mapping and Categorical Principal Components Analysis as two approaches that explore the dimensionality of multiple-choice items in achievement tests. Data from the two forms of the Romanian National Assessment Tests on Science were used to explore the dimensionality of items and to identify potentially problematic items that affect the equivalence of the two parallel forms. The findings confirm that the two tests have at best par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…We selected the number of principal components depending on the specific area of application and the specific data set. However, we used the visual examination of a scree plot approach to determine the number of principal components [36]. Using a scree plot to determine the number of principal components is a common approach, by scanning the scree plot for a point where the amount of variance explained by each subsequent principal component begins to decline.…”
Section: Discussionmentioning
confidence: 99%
“…We selected the number of principal components depending on the specific area of application and the specific data set. However, we used the visual examination of a scree plot approach to determine the number of principal components [36]. Using a scree plot to determine the number of principal components is a common approach, by scanning the scree plot for a point where the amount of variance explained by each subsequent principal component begins to decline.…”
Section: Discussionmentioning
confidence: 99%
“…TAM has been tested and validated in different contexts (Shih et al, 2013) and was extended with different external variables to increase its predictive power (Sepasgozar et al, 2019) resulting into generalized TAM that were reliable and valid as structure (Deliu et al, 2019). However, during this research the results were not found of other in-depth exploration on the adoption of DS tools across pre-service teachers in different national contexts.…”
Section: Introductionmentioning
confidence: 95%